2006
DOI: 10.1186/1471-2350-7-35
|View full text |Cite
|
Sign up to set email alerts
|

Three novel and the common Arg677Ter RP1 protein truncating mutations causing autosomal dominant retinitis pigmentosa in a Spanish population

Abstract: Background: Retinitis pigmentosa (RP), a clinically and genetically heterogeneous group of retinal degeneration disorders affecting the photoreceptor cells, is one of the leading causes of genetic blindness. Mutations in the photoreceptor-specific gene RP1 account for 3-10% of cases of autosomal dominant RP (adRP). Most of these mutations are clustered in a 500 bp region of exon 4 of RP1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 30 publications
(33 reference statements)
4
6
0
Order By: Relevance
“…Also, the phenotype of the patients argues in favour of this finding due to the recessive mutations in the RP1 gene cause an early onset RP 24 . Although there was not antecedents of retinal degeneration in the family, we could confirm the frameshift mutation also in a non-affected sibling supporting the existence of the incomplete penetrance previously reported in this gene 25 . Thus, the identification of the genetic defect becomes increasingly relevant, especially when gene-specific therapeutic approaches are becoming more promising according to the results of the ongoing clinical trials 26 .…”
Section: Discussionsupporting
confidence: 83%
“…Also, the phenotype of the patients argues in favour of this finding due to the recessive mutations in the RP1 gene cause an early onset RP 24 . Although there was not antecedents of retinal degeneration in the family, we could confirm the frameshift mutation also in a non-affected sibling supporting the existence of the incomplete penetrance previously reported in this gene 25 . Thus, the identification of the genetic defect becomes increasingly relevant, especially when gene-specific therapeutic approaches are becoming more promising according to the results of the ongoing clinical trials 26 .…”
Section: Discussionsupporting
confidence: 83%
“…Including our findings, to date 47 RP1 mutations are known to cause adRP. The prevalence of RP1 mutations, with 5.3% in our cohort is similar to the studies reported from United Kingdom and United States, although the prevalence of RP1 mutations varied from 0 to 10% in different adRP cohorts [Baum et al, 2001; Berson et al, 2001; Bowne et al, 1999; Gamundi et al, 2006; Kawamura et al, 2004; Payne et al, 2000; Pierce et al, 1999; Roberts et al, 2006; Sohocki et al, 2001; Sullivan et al, 2006; Zhang et al 2010; Ziviello et al, 2005]. Different pathogenic mechanisms of RP1 truncating mutations have been proposed based on in vitro and in vivo studies leading to ar or adRP.…”
Section: Mutations In the Rp1 Genesupporting
confidence: 88%
“…So far, 43 disease‐causing mutations in RP1 have been identified of which most were found in the last exon, leading to a premature stop codon and are predicted to form a truncated protein (Table 1). The p.Arg677X has been described as the most commonly reported mutation [Baum et al, 2001; Berson et al, 2001; Bowne et al, 1999; Chiang et al, 2006; Gamundi et al, 2006; Guillonneau et al, 1999; Jacobson et al, 2000; Payne et al, 2000; Pierce et al, 1999; Roberts et al, 2006; Schwartz et al, 2003; Sohocki et al, 2001; Sullivan et al, 1999, 2006; Wang et al, 2005; Xiaoli et al, 2002; Ziviello et al, 2005]. Detailed phenotype–genotype correlation of patients with this mutation revealed incomplete penetrance and high variability of disease expression of adRP, suggesting modifiers to be involved [Jacobson et al, 2000].…”
Section: Mutations In the Rp1 Genementioning
confidence: 99%
“…The fact that the vast majority of pathogenic mutations in RP1 result in premature stop codons (nonsense and frameshift mutations) indicate that the most probable adRP-causative mutations in validation sample #8 is p.R667* and not p.E1319G, which might be secondary to the disease and simply reflect the high frequency of carriers harboring heterozygous mutant alleles of IRD genes in the general population [ 24 ]. Additionally, the p.R677* mutation has been reported as the most frequently pathogenic RP1 mutation [ 14 , 25 ] with a location consistent with a dominant inheritance pattern [ 12 ].…”
Section: Discussionmentioning
confidence: 99%